Translation and Theatrical Reception of World Literature in the Jadid Periodicals of Turkestan in the Early Twentieth Century - Teshabaeva, Dilfuza Muminovna; Sabiralieva, Zamira Mametovna (The Lingua Spectrum, 2026)
The article examines how Jadid periodicals in early twentieth-century Turkestan mobilized translation and theatrical culture as interconnected channels for the reception of world literature. It argues that translated fragments, retellings, critical commentary, and theatre-related sections served pedagogical and modernization goals rather than purely aesthetic ones. By privileging compact genres (fable, short story, dialogic scene, essay) and by relying on paratextual infrastructures (subscription notices, book announcements, theatre advertisements), the press shaped a new reader: a disciplined participant in public discussion, trained in causal reasoning and encouraged to apply reading to practical questions of schooling, family ethics, and civic responsibility. Methodologically, the paper combines historical-literary analysis, media history, and a paratextual lens that treats reading infrastructure as a condition of cultural reform. The conclusion is that Jadid engagement with world literature was a strategy of cultural mediation in which translation and theatre functioned as tools for producing modern publicness.